22 Using the adapt-itt model to adapt an evidence-based primary prevention sexual violence intervention from the united states to ghana. (19th September 2017) - Munro-Kramer, Michelle; Rominski, Sarah; Darteh, Eugene; Britwum, Akua; Huhman, Anne; Stephenson, Rob
Abstract : Purpose: Sexual violence is a significant challenge for universities worldwide and prevention programs are non-existent in Ghana. We used the ADAPT-ITT model, a framework to systematically adapt HIV interventions, to adapt a sexual violence prevention program currently used in the United States to a university in Ghana. Methods: The ADAPT-ITT model involves eights steps: (1) Assessment of priorities, (2) Decisions on adapting, (3) Administration of intervention, (4) Production of adapted version, (5) Topical experts, (6) Integration of feedback from topical experts, (7) Training staff to implement, and (8) Testing the adapted intervention. We will focus on steps 1–7 that included the use of focus group discussions (FGDs), cognitive interviews, beta testing, topical expert review, and peer facilitator training. Results: During the Assessment, four FGDs highlighted the themes of (1) body language, (2) expectations of abstinence, (3) gendered power differentials; (4) no means yes, (5) violence and control in marriages, and (6) alcohol's role in sexual violence. Twenty cognitive interviews revealed most of the survey questions were appropriate and well understood. The adapted intervention was Administered to students two times (n=71; n=56). Some pre- and post-test changes were seen in rape myth acceptance, predominantly in males in Round 1, and small but significant changes in views of gender equity, predominantly in females in Round 2. The peer facilitator Training (n=9) demonstrated improvements in self-perceived facilitation skills. Conclusions: Although results are preliminary, this adapted program shows promise in changing attitudes known to be associated with sexual violence perpetration. Future work will include completing a pilot study to fulfil Step 8 of the model. Significance: This is the first study to use the ADAPT-ITT model for a sexual violence intervention. This model holds significant potential to adapt pre-existing evidenced-based interventions in a systematic way for more efficient uptake with new populations and locations.